ÇEKİRDEK KIRMA MAKİNASININ DİZAYNI, İMALAT VE KIRMA VERİMLİLİĞİNİN İNCELENMESİ - TOSUN, NİHAT (Fırat Üniveristesi, 1996)
Bu araştırmada, kayısı ve badem çekirdeklerinin ön elemeli kırılmasını sağlayan bir makinenin tasarımı ve imalatı yapıldı. Ondan sonra çekirdekler; farklı ıslatma sürelerinde (1,2,3 ve 4 saat), farklı çene açıklıklarında (7.5, 7.75, 8, 8.25 ve 8.5 mm) ve farklı devirlerde (50,115, 130 ve 180 d/dak) kırılarak denendi. Maksimum verimi gösteren grafikler hazırlandı. ANAHTAR KELİME: Çekirdek kırma makinası, kayısı.

In this study, a specially stone-cracking machine which breaks stones of apricot and almond with primary sifting designed and manufactured. And then, stones are tested to crack under different wetting periods (1,2,3 and 4 hours), different jaw clearens (7.5, 7.75, 8, 8.25 ve 8.5 mm) and different speeds (50,1 15, 130 and 180 r.p.m.). The maximum efficiency graphics are presented. KEY WORDS: Stone-cracking machine, apricot.
Design and manufacturing of stone-craking machine and its efficiency investigation
Keywords: Makine Mühendisliği; Mechanical Engineering